Kedudukan Hukum Tanah Likuifaksi yang Dijadikan Jaminan Hutang Dalam Akta Perjanjian Pinjam Meminjam - Agustin Veronika Panginja; Anriz N. Halim; Zulki Zulkifli Noor (Postgraduate of Jayabaya University, 2018)
The natural disaster that caused such severe damage was the earthquake in Palu City, Central Sulawesi Province, which occurred on September 28, 2018. Technically, the land reconstruction program after the tsunami disaster faced at least two main problems. First, related to the process of land identification, namely the difficulty in mapping and measuring the boundaries of land that has lost physical markings caused by landfill waste from the rest of natural disasters. Second, related to the credit debt agreement on the Liquidity Land collateral. The research method used in this research is normative juridical supported by empirical data, using normative juridical approach because the target of this study is law or method (norm). Research with normative law objective in the form of legal principles, legal system, vertical and horizontal synchronization level. Research Results Related to the legal status of liquefaction land, the option to relocate affected liquefaction residents must be preceded by geological studies and zoning of spatial planning and disaster mitigation. Relocation means a new location and a new certificate. Because the liquefaction region is in the Red Zone that is not suitable for habitation. Although it has been determined to be included in the designation of a disaster-prone zone (ZRB), the land affected by the faction is still legally owned by local residents. The existence of delays in debtor credit both bank customers and leasing in the Palu region, against victims of the earthquake, liquefaction and tsunami. The governor told the IJK leadership and all Leasing in Central Sulawesi to postpone the debtor's credit at the bank for three years and the leasing debtor's credit for six months. It was an effort to support and help restore the condition of the recording of victims of the earthquake, tsunami and liquefaction natural disasters in Central Sulawesi Province.